Wolman disease presenting with hemophagocytic lymphohistiocytosis syndrome and a novel LIPA gene variant: a case report and review of the literature - Kosar Asna Ashari; Aileen Azari-Yam; Mohammad Shahrooei; Vahid Ziaee (Journal of Medical Case Reports, 2023)
Abstract Background Wolman disease is a rare disease caused by the absence of functional liposomal acid lipase due to mutations in LIPA gene. It presents with organomegaly, malabsorption, and adrenal calcifications. The presentations can resemble hemophagocytic lymphohistiocytosis, the life threatening hyperinflammatory disorder. Since the disease is very rare, clinicians might not think of it when a patient presents with hemophagocytic lymphohistiocytosis, and the opportunity to treat it properly can be lost, thus leading to demise of the child. Case presentation We present a 4.5-month-old Caucasian boy with fever, icterus, and hepatosplenomegaly who was treated according to presumed hemophagocytic lymphohistiocytosis disease. Wolman disease was diagnosed after the death of the child. There are some case reports in the literature presenting patients with Wolman disease primarily diagnosed as hemophagocytic lymphohistiocytosis, which we discuss in this review. The genetic analysis revealed after his demise was compatible with Wolman disease, introducing a novel mutation in LIPA gene: exon 4: NM_001127605: c. G353A (p.G118D), which converts the glycine amino acid to aspartic acid. Conclusions Considering the similarities in presentation of Wolman disease and hemophagocytic lymphohistiocytosis, the patient’s life can be saved if special attention is paid to presenting features of a patient with suspected hemophagocytic lymphohistiocytosis, that is special attention to symptoms, findings on physical exams, laboratory values, and radiologic findings, and the proper treatment is urgently initiated. Reporting the novel mutations of Wolman disease can help geneticists interpret the results of their patients’ genetic studies appropriately, leading to correct diagnosis and treatment.